The changing pattern of fever of unknown origin in the Republic of North Macedonia - Bosilkovski Mile; Dimzova Marija; Cvetkova Marija; Poposki Kostadin; Spasovska Katerina; Vidinic Ivan (Sciendo, 2019)
Introduction. The study aimed to compare the etiologic spectrum of diseases causing fever of unknown origin (FUO) and methods for definitive diagnosis in a tertiary care hospital in the Republic of North Macedonia during two different time periods.